ISLAM AND THE STATE IN INDONESIA: A Sociological and Historical Perspective - Imron Rosyidi (Asia-Pacific Journal on Religion and Society, 2022)
Abstract: This paper presents an analysis of the process of the birth of the new Muslim intellectual generation in Indonesia who prefer cultural to political movements. This new generation promotes a pivotal movement in driving and encouraging changes in the political concept of Pancasila and Islamic state. In Indonesian history, Muslim intellectuals were considered less dominating than Nationalist intellectuals in shaping the form of the state. In the early historyof Indonesian independence, they attempted to promote the  mportance of Islam as the state official ideology. However, since 1970s there had been changes in the orientation of the Muslim intellectuals’ struggle in that they preferred cultural approaches in the shaping of Indonesian state. As a result, many Muslim intellectuals did not have strong eagerness to promote Islam as the state ideology, but still managed to exert their influences to the state through social and professional organizations. As discussed in this paper, one notable example of these organizations is ICMI, whose establishment andgrowth have been significant in recent Indonesian history.